Oxidation behavior of H2 and CO produced by H2O and/or CO2 reduction in molten carbonates: Effect of gas environment and hydroxides. (1st November 2021) - Gürbüz, E.; Albin, V.; Lair, V.; Ringuedé, A.; Cassir, M.
Abstract: Co-electrolysis of water and carbon dioxide in molten carbonates is nowadays a key issue in MCEC (molten carbonate electrolysis cell) and, reversely, for a better understanding of MCFC (molten carbonate fuel cell). The products of water and carbon dioxide reduction are the fuels that might be used in MCFC or other energy devices. The present study is dedicated to a thorough electrochemical investigation by voltammetric techniques (Cyclic Voltammetry CV or Linear Sweep Voltammetry LSV) at a Pt electrode of such fuels in Li2 CO3 -K2 CO3 eutectic, under varied atmosphere conditions, including partial pressures of H2 O, CO2, H2 and Ar at 650°C. The conditions of formation of soluble and/or adsorbed H2 and CO are established together with qualitative thermodynamics information on the redox systems involved. C is only detected in very specific conditions. Knowing that hydroxides, produced in the conditions of MCEC and MCFC, have a significant role on the operation of such devices, an electrochemical analysis (CV and impedance measurements) of the effect of added amounts of hydroxides is developed for the first time, showing the enhancement of oxidation currents and the progressive increase in electrolyte conductivity.